PENGARUH SERVICE QUALITY DAN RELATIOSHIP MARKETING TERHADAP LOYALITAS NASABAH (STUDI KASUS PADA PT. PRUDENTIAL LIFE ASSURANCE PEKANBARU) - Wan Devi Azfarani; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of service quality and relationship marketing on customer loyalty (Case Study PT. Prudential Life Assurance Pekanbaru. Service Quality as a variable (X1) relationship marketing as a variable (X2) and customer loyalty as (Y). The method in this research is descriptive and quantitative using SPSS 20, wherein the samples used are customers of PT. Prudential Life Assurance Pekanbaru by respondents as many as 100 people. The formula used to determine the sample slovin, as well as a sampling technique by purposive sampling. Data collection through questionnaires. Results of analysis using multiple linear regression, t test, and f test. So it can be seen the variable service quality and relationship marketing has positive effect and significant on customer loyalty.Keywords : Brand Image, Brand Trust an Customer loyalty